KESALAHAN PENULISAN KATA BAHASA INDONESIA DALAM JURNAL ILMIAH SAINS DAN TEKNOLOGI - NFN Nursyamsi (Multilingual, 2016)
Variety of scientific language demand obedience in the use of linguistic rules, including writing of articles inscientific journals. The problem of this study was the error in the writing of Indonesian word in Scientific andTechnology Journals. Based on these problems, this study revealed the errors in the writing of Indonesian wordin Scientific and Technology journals and also to fix these errors. The research used library research with analiticdescriptive technique to analyzed the data. Then, the result presented in descriptive method. Based on the results of the discussion found spelling method. The result shows, there are some errors in words writing, such as words writing and foreign expressions, absorption elements, prepositions, affixes words, and combined attached form.